Pengaruh gelombang ultrasonik terhadap nilai kekerasan, laju korosi baja AISI 1020 pada larutan HCl 3,5% setelah proses quenching - Prasetyo, Sugeng; Yuliani, Yuliani; MS, Firdaus (Universitas Muhammadiyah Metro, 2023)
Determination of the value of hardness, corrosion rate and microstructure after the quenching process with variations in immersion time with the help of ultrasonic waves, cooling media in 3,5% HCl solution. The specimens were placed in ultrasonic batches with a frequency of 45 KHz to obtain maximum results. the lowest hardness values ​​in water cooling media occurred at the time of immersion using ultrasonic waves 7 hours, tempering temperatures of 300°C, 400°C and 500°C were 0,6 HRA, 51.2 HRA, 51,6HRA for oil medium of 40 ,3HRA, 41.2HRA, 41.3HRA. While the value of the corrosion rate was obtained the higher the tempering temperature and the length of immersion time the corrosion rate decreased the corrosion rate value in the oil cooling medium was 0.1663 mm/year, 0.1663 mm/year, 0.4726 mm/year, respectively. as well as water cooling media, respectively, namely 0.2125 mm/year, 0.3151mm/year and 0.2538 mm/year. metallographic test results can be a lot of pearly and ferrite formed.